Raf-independent, PP2A-dependent MEK Activation in Response to ERK Silencing - Bae, Dongsoon (2009)
Biological roles of ERK and MEK in signal transduction have been controversial. The aim of the current study was to determine the role of ERK1/2 in signaling through the ERK-MAPK cascade by using RNAi methodology. Transient transfection of erk1 or erk2 siRNA decreased the respective protein level to 3 - 8% in human lung fibroblasts. Interestingly, individual ERK isoform silencing resulted in a 2-fold reciprocal increase in phosphorylation of the alternate ERK isoform, with no change in respective total protein expression. Moreover, MEK was hyperphosphorylated as a result of combined ERK1 and ERK2 silencing, but was unaffected in individual ERK1 or ERK2 silenced cells. This hyperactivation of MEK was not due to activation of Raf family members, but rather was associated with PP2A downregulation. These data highlight the existence of a feedback loop in normal cells whereby ERK silencing is associated with decreased PP2A activity and consequent MEK activation.